Crises of social significances: adolescents and their projects for future work - Petriz, Graciela Mabel; Delucca, Norma Edith (2006)
This is a report on data raised through research, which has already finished, about Identification references in adolescents . Objetives : To analyze and reflect upon the collected data, adolescents' representations about the work field and their projects for future work. To conceptualize about the crises of social significances which produce and order sense and, therefore, organize our perceptions of work through social discourses and practices which have an impact on the subjectivity of adolescents and young adults. Methodology: Brief presentation of the concepts which frame the qualitative research in this area. Reading and analysis of fragments from adolescents' accounts, obtained in focal groups at different state secondary schools. Conclusions: The adolescents researched portray a self-image full of uncertainty and skepticism as regards their future possibilities. The impact produced by the fall of work as an ideal of doing and being is made evident in their accounts. Only some of them link their future project with an invested and valuable activity, even if this is not associated with economic safety and wellbeing. Others present themselves as incapable to modify the state of things, which offers a field connected with consumerist values and with the idea that "you are worth what you have (in material things)".
Keywords: Representations; Adolescent; Work; Future projects; Social significances